Scarface [videorecording (Blu-Ray)] - Stone, Oliver; Pacino, Al, 1940-; Pfeiffer, Michelle, 1957-; Bauer, Steven, 1956-; Mastrantonio, Mary Elizabeth; Abraham, F. Murray; Loggia, Robert (Universal Pictures Home Entertainment, 2019)
In the spring of 1980, the port at Mariel Harbor was opened, and thousands set sail for the United States. They came in search of the American Dream. One of them found it on the sun-washed avenues of Miami; wealth, power and passion beyond his wildest dreams. He was Tony Montana. The world will remember him by another name. Starring Al Pacino as Tony Montana, this film has become a cultural phenomenon brilliantly directed by Brian De Palma and written by Oliver Stone.--Adapted from container.